Leaching strategies for Si and Al impurity management during industrial black mass processing - Yuanmin Zou; Herrala Reima; Benjamin P. Wilson; Mari Lundström (Journal of Environmental Chemical Engineering, 2026)

Ecotonal gradients shape biodiversity of multiple estuarine taxa - Rebecca Oester; Benjamin Branoff; Johanna Biederbick; Luise Grüterich; Raphael Koll; Fay Lexmond; Nele Martens; Julian Mittmann-Goesele; Friederike Neiske; Widhi Putri; Sina Remmers; Diana Richter; et al. (Estuarine, Coastal and Shelf Science, 2026)

Correction: The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Dietary curcumin supplementation impacts on growth performance, antioxidant status, and immune response of seabass (Dicentrarchus labrax) larvae - Hien-La Nguyen The; Wilson Pinto; Ana Teresa Gonçalves; Gabriella do Vale Pereira; Inês Freitas; Sara Castanho; Cátia Lourenço-Marques; Florbela Soares; Bruno Reis; Benjamin Costas; Pedro Pousão-Ferreira; Luís E. C. Conceição (Fish Physiology and Biochemistry, 2026)

Plasma pTau181 is associated with subjective cognitive concerns but not objective cognitive decline or structural brain integrity measures in midlife - Ashleigh Barrett-Young; Erin E. Cawston; Brigid Ryan; Wickliffe C. Abraham; Antony Ambler; Tim Anderson; Kirsten Cheyne; Elizabeth Goodin; Sean Hogan; Renate M. Houts; David Ireland; Annchen R. Knodt; et al. (GeroScience, 2026)
Although plasma pTau181 has been shown to accurately discriminate patients with Alzheimer’s disease from healthy older adults, there are few studies of plasma biomarkers among middle-aged populations. Given the potential utility of plasma AD biomarkers such as pTau181 in screening for disease risk, examining pTau181 in a middle-aged cohort without AD is important for future implementation. The objectives of this study were to characterise plasma pTau181 in a middle-aged birth cohort aged 45 years and to investigate associations with early indicators of dementia risk. Participants were members of the Dunedin Multidisciplinary Health and Development Study, a longitudinal study of 1037 people born in New Zealand in 1972–1973. Plasma pTau181, self-reported cognitive concerns, MRI-based brain structure, and DunedinPACE (an epigenetic biomarker of biological ageing) were measured at age 45; cognition was measured in childhood and age 45. Plasma pTau181 concentrations at age 45 ( n = 854, 49% female) were associated with self-reported cognitive concerns (β = 0.09, p = .008); however, no significant associations were observed with objective cognitive decline, worse structural brain integrity, or biological ageing. Higher plasma pTau181 was associated with self-reported cognitive concerns at age 45, but not objective AD-related measures. The association of plasma pTau181 and self-reported cognitive concerns in this cohort suggests that AD pathology may begin to accumulate by age 45 and may be associated with subtle changes in cognition that are not at objectively measurable levels. Graphical Abstract

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Effect of leaching reductants on the environmental impacts of an advanced hydrometallurgical battery recycling process - Heikki Lappalainen; Marja Rinne; Heini Elomaa; Jari Aromaa; Benjamin P. Wilson; Mari Lundström (Journal of Cleaner Production, 2026)

Examining Marine Assemblages Across an Inverse Salinity Gradient - Kirsty E. Richards; Simon Jarman; Benjamin J. Saunders; Shaun Wilson; Euan S. Harvey (Molecular Ecology, 2026)
Salinity gradients and fluctuations can create a natural ecological filter, with few species tolerating salinity above 50 practical salinity units (PSUs). We investigated how an inverse salinity gradient affected marine community diversity and composition in Shark Bay, a remote hypersaline coastal embayment in Western Australia. We used 16S(fish), 18S and 16S(Bacteria) eDNA metabarcoding assays to analyse genetic sequences collected from 220 surface water samples and 216 benthic roller samples. The 44 survey sites encompassed a salinity gradient of 40.1 PSU in the Eastern Gulf to 76.0 PSU in Hamelin Pool. 24,011,345 eDNA sequencing reads were detected from 5575 operational taxonomic units (OTUs). The number of Families and OTUs, and OTUs within key Phyla, all decreased with increasing salinity, the most dramatic changes occurring over a narrow salinity range (50–60 PSU). However, the relative proportion of Families from each Phyla contributing to the total assemblage within each salinity range remained relatively stable. Key processes may therefore be maintained across the salinity gradient, although redundancy and resilience are compromised as diversity declines and the taxonomic composition of the communities changes. Although primary producers such as cyanobacteria, seagrass and the bivalve mollusc Fragum spp. were under‐represented within our data set, this may be due to a limitation of the eDNA methods used rather than their absence within the ecosystem. Even with these limitations, eDNA has proven a useful tool for examining the whole marine assemblage across an inverse salinity gradient in a remote area at a broad taxonomic level.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Restoring the wild east: Predicting public support for cougar and red wolf reintroduction in the eastern United States - Benjamin Ghasemi; Jeremy T. Bruskotter; John A. Vucetich; L. Mark Elbroch; Robyn S. Wilson; Neil H. Carter; Axel Moehrenschlager; Shelby Perry; Joseph W. Hinton (Biological Conservation, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Repeated low-dose copper algaecide treatments promote beneficial phytoplankton and zooplankton communities - Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Journal of Environmental Management, 2025)

Think globally, barcode locally: nine years of macrofungi sampling reveals extensive biodiversity at the ordway-swisher biological station, a subtropical site in Florida - Marcos V. Caiafa; Laurel Kaminsky; Rosanne Healy; Leanne P. Sheffer; C. Benton Willis; Katy Deitz; Brantlee S. Richter; Benjamin R. Lemmond; David Borland; Bitty A. Roy; Heather A. Dawson; Carolyn A. Delevich; et al. (Fungal Biology, 2025)

Locally Reprogramming Tumor-Associated Macrophages with Cytokine-Loaded Injectable Cryogels for Breast Cancer - Sydney R. Henriques; Evan B. Glass; Kristen L. Hoek; Ori Z. Chalom; Abigail E. Manning; Sohini Roy; Diana K. Graves; Sarah M. Goldstein; Benjamin C. Hacker; Renjie Jin; Marjan Rafat; Paula J. Hurley; et al. (Annals of Biomedical Engineering, 2025)
Purpose Tumor-associated macrophages (TAMs) are the most abundant immune cells in primary solid tumors, including breast cancer, and typically exhibit an M2-like, immunosuppressive phenotype that promotes tumor growth. Given that TAMs can be repolarized through cytokine signaling, we propose a localized cytokine delivery depot using an injectable alginate cryogel to reprogram TAMs and create an inflammatory, anti-tumor TME. Methods The cryogels were fabricated using cryogelation to generate a macroporous structure, followed by ionic crosslinking to enhance mechanical integrity while preserving pore size distribution. In vitro studies were conducted using bone marrow-derived macrophages, tumor-associated macrophages, and tumor explants. In vivo studies were conducted by orthotopically implanting breast tumors in the fat pads of FVB mice. Cell makeup and tissue composition were analyzed using qRT-PCR, flow cytometry, and Luminex panels. Statistical significance was determined using ANOVA and t -tests. Results In vitro, cryogels released chemokines and cytokines, attracted M2 macrophages, and repolarized them toward M1-like activities. In vivo, cryogel treatment increased the presence of M1 macrophages relative to M2 macrophages in both the primary tumor and lungs, reduced primary tumor growth, and decreased T-cell exhaustion. Conclusions A localized, injectable cryogel depot successfully induces an inflammatory TME, leading to reduced tumor burden and T-cell exhaustion while avoiding systemic toxicities associated with cytokine delivery.

A Safe Operating Space for Salmon Watersheds Under Rapid Climate Change - Jonathan W. Moore; Marta E. Ulaski; Kyle L. Wilson; Tara G. Martin; Spencer Dakin Kuiper; Stephanie J. Peacock; Douglas C. Braun; Sean M. Naman; Kara J. Pitman; Andrea J. Reid; Jordan S. Rosenfeld; Nigel C. Sainsbury; et al. (Fish and Fisheries, 2025)
Climate change and local pressures are eroding the health and performance of many watersheds and their freshwater ecosystems, pushing these complex social‐ecological systems to the boundaries of their safe operating space. Here, we offer a synthetic perspective on the downscaled application of the safe operating space concept to inform the stewardship of watersheds in this time of rapid climate change, with particular focus on watersheds that support coldwater migratory fishes such as Pacific salmon. First, we review the safe operating space concept as it applies to salmon watersheds as social‐ecological systems. Salmon watersheds, and the benefits they provide for diverse peoples, are under enormous cumulative pressure from climate change as well as local activities such as forestry, urbanisation, mining and agriculture. We identify four general syndromes of dual local and climate pressures. For example, local pressures, such as the removal of riparian vegetation that shades streams, can exacerbate climate warming of water temperatures. Furthermore, extractive industries can damage or destroy future habitats and thus erode adaptive capacity. As an illustrative example of how the safe operating space concept can be operationalised, we assess alternative plausible watershed futures of land use and climate change scenarios and salmon performance. Collectively, this work showcases tangible options for local management to help give salmon watersheds the time and space to cope with climate change. More broadly, while there is a global need to address climate change, local watershed management is a key component of pathways towards freshwater sustainability and their services for humanity.

Correction: Locally Reprogramming Tumor-Associated Macrophages with Cytokine-Loaded Injectable Cryogels for Breast Cancer - Sydney R. Henriques; Evan B. Glass; Kristen L. Hoek; Ori Z. Chalom; Abigail E. Manning; Sohini Roy; Diana K. Graves; Sarah M. Goldstein; Benjamin C. Hacker; Renjie Jin; Marjan Rafat; Paula J. Hurley; et al. (Annals of Biomedical Engineering, 2025)

Some like it salty - examining fish assemblages across an extreme salinity gradient, Shark Bay, Western Australia - Kirsty E. Richards; Benjamin J. Saunders; Erica Suosaari; Shaun Wilson; Euan S. Harvey (Marine Environmental Research, 2025)

Misalignment in the automotive supply Chain: Sustainability commitments of automotive manufacturing firms and their suppliers - David Benjamin Billedeau; Jeffrey Wilson (Journal of Cleaner Production, 2025)

Life cycle assessment of enhanced materials recovery from LTO-rich anode waste recycling via froth flotation - Diana Arellano-Sanchez; Marja Rinne; Luis Arturo Gomez-Moreno; Benjamin P. Wilson; Rodrigo Serna-Guerrero; Mari Lundström (Minerals Engineering, 2025)

Temporal assessment of fish distribution and abundance in a hypersaline embayment, Hamelin Pool, Shark Bay, Western Australia - Kirsty E. Richards; Kelly L. Campbell; Benjamin J. Saunders; Erica P. Suosaari; Shaun K. Wilson; Euan S. Harvey (Estuarine, Coastal and Shelf Science, 2025)

Investigation of field and laboratory-based personality traits in a wild ornate box turtle (Terrapene ornata) population - Brianna Wilson; Samantha Kim; Abigail Trautman; Katie Brighton; Erica Guldner; Zoe Edlund; Patience Wagner; Timothy Speer; Keetan Munsell; Rodrigo J. Mercader; Benjamin M. Reed (Behavioral Ecology and Sociobiology, 2025)

Suitability of assessing population-level impacts from construction of a single wind farm – a case study on North Sea harbour porpoises - N. C. F. van Geel; S. Benjamins; B. Marmo; J. Nabe-Nielsen; A. Wittich; D. Risch; V. L. G. Todd; B. Wilson (Frontiers in Marine Science, 2025)
Continued development of offshore renewable energy is urgently needed to support the goal of achieving global Net Zero targets; however, concerns persist about impacts of construction noise on acoustically sensitive species such as the harbour porpoise ( Phocoena phocoena ). Population impact modelling frameworks have been proposed as a quantitative way to evaluate whether disturbance, as experienced by individual animals, might result in negative population-level consequences, and suggested as useful tools in support of Environmental Impact Assessments. However, questions remain regarding model applicability to projects of different spatial scales. This study applied two such models (iPCoD and DEPONS) to assess potential population-level impacts of construction of the East Anglia ONE wind farm on North Sea harbour porpoises. Both models were parameterised using project-specific input values underpinned by static passive acoustic monitoring data. The various iPCoD and DEPONS scenario simulations did not predict any long-term population-level impacts in response to pin-piling activities. This is likely due to discrepancy in scale between localised, short-term impacts of constructing a single wind farm in comparison to the range of the North Sea porpoise population. DEPONS modelling also revealed no long-term negative impact of pin-piling on predicted porpoise numbers within the boundary of the Southern North Sea Special Area of Conservation. Current results highlight the importance of scale when using either modelling framework to evaluate the likelihood of long-term population-level impacts on abundant, wide-ranging species from individual offshore renewables developments. Cumulative population effects from human activities, including other construction projects, commercial shipping, hydrocarbon exploitation, and fisheries bycatch, are not well understood but can be approached with the modelling frameworks explored here. However, such effects will not be apparent when applying these models to individual construction projects and in isolation from coexisting pressures. There is a risk that ignoring co-occurring pressures may result in an incomplete picture of simulated population trajectories that should be considered carefully when these models are proposed to evaluate impacts of offshore renewable construction projects. We advocate that long-term population impact modelling should be applied on a regional basis and take additional wind farm developments as well as other cumulative pressures into consideration.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Life cycle assessment of LTO-rich anode waste from lithium-ion battery with a hazardous waste management approach - Diana Arellano-Sanchez; Marja Rinne; Benjamin P. Wilson; Mari Lundström (Resources, Conservation and Recycling, 2025)

Evaluating the tolerance of harmful algal bloom communities to copper - Ashley V. Hennessey; Michael B. McDonald; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Environmental Pollution, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

An investigation of an outbreak of Salmonella Typhimurium infections linked to cantaloupe – United States, 2022 - Sharon Seelman Federman; Erin Jenkins; Cullen Wilson; Arturo DeLaGarza; Colin Schwensohn; Benjamin Schneider; Johnson Nsubuga; Robert Literman; Allison Wellman; Brooke M. Whitney; Rebecca L. Bell; Kerri Harris-Garner; et al. (Food Control, 2024)

An analysis of built environment characteristics in daily activity spaces and associations with bike share use - Benjamin G. Ethier; Jeffrey S. Wilson; Sarah M. Camhi; Ling Shi; Philip J. Troped (Travel Behaviour and Society, 2024)

Investigating battery black mass leaching performance as a function of process parameters by combining leaching experiments and regression modeling - Jere Partinen; Petteri Halli; Anna Varonen; Benjamin P. Wilson; Mari Lundström (Minerals Engineering, 2024)

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Electrochemical cobalt oxidation in chloride media - Iryna Makarava; Jere Vänskä; Agnieszka Kramek; Jacek Ryl; Benjamin P. Wilson; Kirsi Yliniemi; Mari Lundström (Minerals Engineering, 2024)

Gold recovery from cyanidation residue by chloride leaching and carbon adsorption – Preliminary results from CICL process - Anssi Karppinen; Sipi Seisko; Laura Nevatalo; Benjamin P. Wilson; Kirsi Yliniemi; Mari Lundström (Hydrometallurgy, 2024)

Studying interactions among anthropogenic stressors in freshwater ecosystems: A systematic review of 2396 multiple‐stressor experiments - James A. Orr; Samuel J. Macaulay; Adriana Mordente; Benjamin Burgess; Dania Albini; Julia G. Hunn; Katherin Restrepo‐Sulez; Ramesh Wilson; Anne Schechner; Aoife M. Robertson; Bethany Lee; Blake R. Stuparyk; et al. (Ecology Letters, 2024)
Understanding the interactions among anthropogenic stressors is critical for effective conservation and management of ecosystems. Freshwater scientists have invested considerable resources in conducting factorial experiments to disentangle stressor interactions by testing their individual and combined effects. However, the diversity of stressors and systems studied has hindered previous syntheses of this body of research. To overcome this challenge, we used a novel machine learning framework to identify relevant studies from over 235,000 publications. Our synthesis resulted in a new dataset of 2396 multiple‐stressor experiments in freshwater systems. By summarizing the methods used in these studies, quantifying trends in the popularity of the investigated stressors, and performing co‐occurrence analysis, we produce the most comprehensive overview of this diverse field of research to date. We provide both a taxonomy grouping the 909 investigated stressors into 31 classes and an open‐source and interactive version of the dataset ( https://jamesaorr.shinyapps.io/freshwater‐multiple‐stressors/ ). Inspired by our results, we provide a framework to help clarify whether statistical interactions detected by factorial experiments align with stressor interactions of interest, and we outline general guidelines for the design of multiple‐stressor experiments relevant to any system. We conclude by highlighting the research directions required to better understand freshwater ecosystems facing multiple stressors.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

A study on recovery strategies of graphite from mixed lithium-ion battery chemistries using froth flotation - Hanna Sahivirta; Benjamin P. Wilson; Mari Lundström; Rodrigo Serna-Guerrero (Waste Management, 2024)

A Review of Unmanned Aerial Vehicles Usage as an Environmental Survey Tool within Tidal Stream Environments - James Slingsby; Beth E. Scott; Louise Kregting; Jason McIlvenny; Jared Wilson; Benjamin J. Williamson (Journal of Marine Science and Engineering, 2023)
Tidal energy is a rapidly developing area of the marine renewable energy sector that requires converters to be placed within areas of fast current speeds to be commercially viable. Tidal environments are also utilised by marine fauna (marine mammals, seabirds and fish) for foraging purposes, with usage patterns observed at fine spatiotemporal scales (seconds and metres). An overlap between tidal developments and fauna creates uncertainty regarding the environmental impact of converters. Due to the limited number of tidal energy converters in operation, there is inadequate knowledge of marine megafaunal usage of tidal stream environments, especially the collection of fine-scale empirical evidence required to inform on and predict potential environmental effects. This review details the suitability of using multirotor unmanned aerial vehicles within tidal stream environments as a tool for capturing fine-scale biophysical interactions. This includes presenting the advantages and disadvantages of use, highlighting complementary image processing and automation techniques, and showcasing the limited current examples of usage within tidal stream environments. These considerations help to demonstrate the appropriateness of unmanned aerial vehicles, alongside applicable image processing, for use as a survey tool to further quantify the potential environmental impacts of marine renewable energy developments.

The impact of chlorides on NMC leaching in hydrometallurgical battery recycling - Jere Partinen; Petteri Halli; Benjamin P. Wilson; Mari Lundström (Minerals Engineering, 2023)

Global genomic signature reveals the evolution of fall armyworm in the Eastern hemisphere - Lei Zhang; Zaiyuan Li; Yan Peng; Xinyue Liang; Kenneth Wilson; Gilson Chipabika; Patrick Karangwa; Bellancile Uzayisenga; Benjamin A. Mensah; Donald L. Kachigamba; Yutao Xiao (Molecular Ecology, 2023)
The major plant pest fall armyworm (FAW), Spodoptera frugiperda, is native to the Americas and has colonized Africa and Asia within the Eastern hemisphere since 2016, causing severe damage to multiple agricultural crop species. However, the genetic origin of these invasive populations requires more in‐depth exploration. We analysed genetic variation across the genomes of 280 FAW individuals from both the Eastern hemisphere and the Americas. The global range‐wide genetic structure of FAW shows that the FAW in America has experienced deep differentiation, largely consistent with the Z‐chromosomal Tpi haplotypes commonly used to differentiate ‘corn‐strain’ and ‘rice‐strain’ populations. The invasive populations from Africa and Asia are different from the American ones and have a relatively homogeneous population structure, consistent with the common origin and recent spreading from Africa to Asia. Our analyses suggest that north‐ and central American ‘corn‐strain’ FAW are the most likely sources of the invasion into the Eastern hemisphere. Furthermore, evidence based on genomic, transcriptomic and mitochondrial haplotype network analyses indicates an earlier, independent introduction of FAW into Africa, with subsequent migration into the recent invasive population.

Millimetre‐scale pollen analysis of non‐varved lacustrine sediments from Onepoto maar palaeolake, Auckland, reveals distal vegetation responses and landscape recovery following the ~25.5‐ka Ōruanui supereruption, New Zealand - Stephen B. Piva; Simon J. Barker; Rewi M. Newnham; Andrew B. H. Rees; Colin J. N. Wilson; Lionel Carter; Nels A. Iverson; Benjamin Läuchli; Paul C. Augustinus (Journal of Quaternary Science, 2023)
The ~25.5‐ka Ōruanui supereruption (Taupō volcano, New Zealand) erupted >1100 km 3 of pyroclastic material during the Last Glacial Maximum. The impacts of this event on climate and the New Zealand environment remain unresolved, particularly on ecological timescales. Using sediment cores from Onepoto maar palaeolake, Auckland (~240 km upwind from source), we have analysed pollen assemblages at contiguous 1‐mm intervals, around an intact 3‐cm layer of the Kawakawa‐Ōruanui Tephra to resolve and assess post‐eruption vegetation impacts and landscape recovery. Sediments immediately above the tephra record a decline in the relative abundance of the dominant canopy species of Fuscospora , and concurrent increase in the abundances of grasses, herbs, ferns and shrubs. These changes reflect a brief (

Occurrence of Rickettsia spp. and Coxiella burnetii in ixodid ticks in Kassena-Nankana, Ghana - Seth Offei Addo; Ronald Essah Bentil; Bernice Olivia Ama Baako; Kevin Nii Yartey; Eric Behene; Benjamin Asiamah; Abena Akyeamaa Nyarko; Victor Asoala; Mohamed Sallam; Suzanne Mate; James C. Dunford; John Asiedu Larbi; et al. (Experimental and Applied Acarology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

Using Unmanned Aerial Vehicle (UAV) Imagery to Characterise Pursuit-Diving Seabird Association With Tidal Stream Hydrodynamic Habitat Features - James Slingsby; Beth E. Scott; Louise Kregting; Jason McIlvenny; Jared Wilson; Marion Yanez; Samuel Langlois; Benjamin J. Williamson (Frontiers in Marine Science, 2022)
Tidal stream environments exhibit fast current flows and unique turbulent features occurring at fine spatio-temporal scales (metres and seconds). There is now global recognition of the importance of tidal stream environments for marine megafauna. Such areas are also key to the development of marine renewable energy due to the reliable and predictable nature of tidally driven flows. Bed-derived turbulent features, such as kolk-boils, transport organic material to the surface and may increase the availability of prey species (fish) for foraging marine megafauna (seabirds and marine mammals). Quantification of animal association and interactions with turbulent features is required to understand potential environmental impacts of tidal energy developments in these sites. Downward-facing unmanned aerial vehicle (UAV) imagery was collected within the Pentland Firth, UK. Resulting imagery was used to quantify the density distribution of pursuit-diving seabirds, called auks (of the family Alcidae), distribution in comparison relation to concurrent surface imagery of kolk-boils and, analyse evaluate spatial relationships with individual kolk-boil features, and quantify body orientation relative to the water flow. Although variability was present, auk density distribution was generally correlated with that of kolk-boils throughout the study area; however, spatial analysis highlighted an overall trend of finer-scale dispersion between individual auks and kolk-boils. Auk orientation on the surface was primarily observed across the flow throughout ebb and flood tidal phases. These results suggest that auks may be associating with kolk-boil peripheries. Similarly, it may be energetically beneficial to orientate across the flow while maintaining observation of current flow or searching for shallow prey species and potential threats in the environment. This work demonstrates that UAV imagery was appropriate for quantification of fine-scale biophysical interactions. It allowed for concurrent measurement of hydrodynamic and predator metrics in a challenging environment and provided novel insights not possible to collect by conventional survey methodology. This technique can increase the evidence base for assessment of potential impacts of marine renewable energy extraction on key marine species.

Isotopic and geochemical tracers of groundwater flow in the Shivwits Plateau, Grand Canyon National Park, USA - Jonathan W. Wilson; Andrea M. Erhardt; Benjamin W. Tobin (Hydrogeology Journal, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Psychological distress in response to physical activity restrictions in patients with non-syndromic thoracic aortic aneurysm/dissection - Alexis McEntire; Benjamin M. Helm; Benjamin J. Landis; Lindsey R. Elmore; Theodore Wilson; Leah Wetherill; Stephanie M. Ware (Journal of Community Genetics, 2021)

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

Modeling Small Scale Impacts of Multi-Purpose Platforms: An Ecosystem Approach - Natalia Serpetti; Steven Benjamins; Stevie Brain; Maurizio Collu; Bethany J. Harvey; Johanna J. Heymans; Adam D. Hughes; Denise Risch; Sophia Rosinski; James J. Waggitt; Ben Wilson (Frontiers in Marine Science, 2021)
Aquaculture and marine renewable energy are two expanding sectors of the Blue Economy in Europe. Assessing the long-term environmental impacts in terms of eutrophication and noise is a priority for both the EU Water Framework Directive and the Marine Strategy Framework Directive, and cumulative impacts will be important for the Maritime Spatial Planning under the Integrated Maritime Policy. With the constant expansion of aquaculture production, it is expected that farms might be established further offshore in more remote areas, as high-energy conditions offer an opportunity to generate more power locally using Marine Renewable Energy (MRE) devices. A proposed solution is the co-location of MRE devices and aquaculture systems using Multi-Purpose Platforms (MPPs) comprising offshore wind turbines (OWTs) that will provide energy for farm operations as well as potentially shelter the farm. Disentangling the impacts, conflicts and synergies of MPP elements on the surrounding marine ecosystem is challenging. Here we created a high-resolution spatiotemporal Ecospace model of the West of Scotland, in order to assess impacts of a simple MPP configuration on the surrounding ecosystem and how these impacts can cascade through the food web. The model evaluated the following specific ecosystem responses: (i) top-down control pathways due to distribution changes among top-predators (harbor porpoise, gadoids and seabirds) driven by attraction to the farming sites and/or repulsion/killing due to OWT operations; (ii) bottom-up control pathways due to salmon farm activity providing increasing benthic enrichment predicated by a fish farm particle dispersal model, and sediment nutrient fluxes to the water column by early diagenesis of organic matter (recycled production). Weak responses of the food-web were found for top-down changes, whilst the results showed high sensitivity to increasing changes of bottom-up drivers that cascaded through the food-web from primary producers and detritus to pelagic and benthic consumers, respectively. We assessed the sensitivity of the model to each of these impacts and the cumulative effects on the ecosystem, discuss the capabilities and limitations of the Ecospace modeling approach as a potential tool for marine spatial planning and the impact that these results could have for the Blue Economy and the EU’s New Green Deal.

Pathogenic variants in CDH11 impair cell adhesion and cause Teebi hypertelorism syndrome - Dong Li; Michael E. March; Paola Fortugno; Liza L. Cox; Leticia S. Matsuoka; Rosanna Monetta; Christoph Seiler; Louise C. Pyle; Emma C. Bedoukian; María José Sánchez-Soler; Oana Caluseriu; Katheryn Grand; et al. (Human Genetics, 2021)

Microbial diversity and activity in Southern California salterns and bitterns: analogues for remnant ocean worlds - Benjamin Klempay; Nestor Arandia‐Gorostidi; Anne E. Dekas; Douglas H. Bartlett; Christopher E. Carr; Peter T. Doran; Avishek Dutta; Natalia Erazo; Luke A. Fisher; Jennifer B. Glass; Alexandra Pontefract; Sanjoy M. Som; et al. (Environmental Microbiology, 2021)
Summary Concurrent osmotic and chaotropic stress make MgCl 2 ‐rich brines extremely inhospitable environments. Understanding the limits of life in these brines is essential to the search for extraterrestrial life on contemporary and relict ocean worlds, like Mars, which could host similar environments. We sequenced environmental 16S rRNA genes and quantified microbial activity across a broad range of salinity and chaotropicity at a Mars‐analogue salt harvesting facility in Southern California, where seawater is evaporated in a series of ponds ranging from kosmotropic NaCl brines to highly chaotropic MgCl 2 brines. Within NaCl brines, we observed a proliferation of specialized halophilic Euryarchaeota, which corresponded closely with the dominant taxa found in salterns around the world. These communities were characterized by very slow growth rates and high biomass accumulation. As salinity and chaotropicity increased, we found that the MgCl 2 ‐rich brines eventually exceeded the limits of microbial activity. We found evidence that exogenous genetic material is preserved in these chaotropic brines, producing an unexpected increase in diversity in the presumably sterile MgCl 2 ‐saturated brines. Because of their high potential for biomarker preservation, chaotropic brines could therefore serve as repositories of genetic biomarkers from nearby environments (both on Earth and beyond) making them prime targets for future life‐detection missions.

Biology and genetic diversity of phasey bean mild yellows virus, a common virus in legumes in Australia - Murray Sharman; Andrew S. Appiah; Fiona Filardo; Narelle Nancarrow; Benjamin S. Congdon; Monica Kehoe; Mohammad Aftab; Robert S. Tegg; Calum R. Wilson (Archives of Virology, 2021)

Central Asian wild tulip conservation requires a regional approach, especially in the face of climate change - Brett Wilson; Aibek Dolotbakov; Benjamin J. Burgess; Colin Clubbe; Georgy Lazkov; Kaiyrkul Shalpykov; Myskalai Ganybaeva; Ormon Sultangaziev; Samuel F. Brockington (Biodiversity and Conservation, 2021)
Tulips ( Tulipa spp.) are one of the most widely appreciated plants worldwide, nevertheless species taxonomy and biogeography are often poorly understood. Most wild tulips inhabit the mountains of Central Asia, a recognised biodiversity hotspot, and a centre of tulip diversity. Despite the presence of several country-level endemic Tulipa species, most taxa span the borders of several nations. With no globally Red Listed tulip taxa from this region national level conservation assessments are an important resource. Nonetheless, threats posed to tulips are still inadequately understood, especially climate change, and given the trans-national nature of most species, distributional information is restricted and often misleading. Here we collate 330 species records from the Global Biodiversity Information Facility with 85 newly collected records, to undertake species distribution modelling (MaxEnt) for ten native Central Asian species. This work showed that regional level models provide a much more comprehensive understanding of species’ extinction risks, proportions of habitat in different countries, and limitations in protected area coverage. Furthermore, our climate modelling, the first of its kind for tulips, suggests that climate change will have a significant negative impact on the range size of all species; including those that are currently widespread. We therefore add climate change to the list of threats affecting tulip populations in Central Asia, which already includes livestock overgrazing, urbanisation, wild collection, and mining. Overall, our work shows that although national information is important, a regional approach is crucial not just for tulip conservation efforts, but likely for Central Asian plant conservation in general.

Surface Characterisation of Kolk-Boils within Tidal Stream Environments Using UAV Imagery - James Slingsby; Beth E. Scott; Louise Kregting; Jason McIlvenny; Jared Wilson; Ana Couto; Deon Roos; Marion Yanez; Benjamin J. Williamson (Journal of Marine Science and Engineering, 2021)
High-flow tidal stream environments, targeted for tidal turbine installations, exhibit turbulent features, at fine spatio-temporal scales (metres and seconds), created by site-specific topography and bathymetry. Bed-derived turbulent features (kolk-boils) are thought to have detrimental effects on tidal turbines. Characterisation of kolk-boils is therefore essential to inform turbine reliability, control, and maintenance strategies. It will also improve the understanding of potential ecological interactions with turbines, as marine animals use these sites for foraging. Unmanned aerial vehicle (UAV), or drone, imagery offers a novel approach to take precise measurements of kolk-boil characteristics (distribution, presence, and area) at the surface. This study carried out sixty-three UAV surveys within the Inner Sound of the Pentland Firth, Scotland, UK, over four-day periods in 2016 and 2018. Kolk-boil characteristics were examined against relevant environmental covariates to investigate potential drivers of presence and area. The results show that distribution at the surface could be predicted based on tidal phase, with current velocity significantly influencing presence above 3.0 m/s. The technique can be used to inform turbine development, micro-siting and provide better understanding of environmental implications of turbine operation. Finally, it highlights the suitability of UAVs for capturing rapid fine-scale hydrodynamic data in the absence of in situ measurements.

Variation in herbivore grazing behavior across Caribbean reef sites - Margaret W. Wilson; Steven D. Gaines; Adrian C. Stier; Benjamin S. Halpern (Marine Biology, 2021)
Herbivorous fish can increase coral growth and survival by grazing down algal competitors. With coral reefs in global decline, maintaining adequate herbivory has become a primary goal for many managers. However, herbivore biomass targets assume grazing behavior is consistent across different reef systems, even though relatively few have been studied. We document grazing behavior of two scarid species in Antigua, Barbuda, and Bonaire. Our analyses show significant differences in intraspecific feeding rates, time spent grazing, and intensity of grazing across sites, which may alter the ecological impact of a given scarid population. We suggest several hypothesized mechanisms for these behavioral variations that would benefit from explicit testing in future research. As managers set targets to enhance herbivory on reefs, it is critical that we understand potential differences in scarid grazing impact. Our findings demonstrate the variability of grazing behavior across different reef sites and call for further investigation of the drivers and ecological implications of these inconsistencies.

The Use of Animal-Borne Biologging and Telemetry Data to Quantify Spatial Overlap of Wildlife with Marine Renewables - Natalie Isaksson; Ian R. Cleasby; Ellie Owen; Benjamin J. Williamson; Jonathan D. R. Houghton; Jared Wilson; Elizabeth A. Masden (Journal of Marine Science and Engineering, 2021)
The growth of the marine renewable energy sector requires the potential effects on marine wildlife to be considered carefully. For this purpose, utilization distributions derived from animal-borne biologging and telemetry data provide accurate information on individual space use. The degree of spatial overlap between potentially vulnerable wildlife such as seabirds and development areas can subsequently be quantified and incorporated into impact assessments and siting decisions. While rich in information, processing and analyses of animal-borne tracking data are often not trivial. There is therefore a need for straightforward and reproducible workflows for this technique to be useful to marine renewables stakeholders. The aim of this study was to develop an analysis workflow to extract utilization distributions from animal-borne biologging and telemetry data explicitly for use in assessment of animal spatial overlap with marine renewable energy development areas. We applied the method to European shags (Phalacrocorax aristotelis) in relation to tidal stream turbines. While shag occurrence in the tidal development area was high (99.4%), there was no overlap (0.14%) with the smaller tidal lease sites within the development area. The method can be applied to any animal-borne bio-tracking datasets and is relevant to stakeholders aiming to quantify environmental effects of marine renewables.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Ecological impacts of human‐induced animal behaviour change - Margaret W. Wilson; April D. Ridlon; Kaitlyn M. Gaynor; Steven D. Gaines; Adrian C. Stier; Benjamin S. Halpern (Ecology Letters, 2020)
A growing body of literature has documented myriad effects of human activities on animal behaviour, yet the ultimate ecological consequences of these behavioural shifts remain largely uninvestigated. While it is understood that, in the absence of humans, variation in animal behaviour can have cascading effects on species interactions, community structure and ecosystem function, we know little about whether the type or magnitude of human‐induced behavioural shifts translate into detectable ecological change. Here we synthesise empirical literature and theory to create a novel framework for examining the range of behaviourally mediated pathways through which human activities may affect different ecosystem functions. We highlight the few empirical studies that show the potential realisation of some of these pathways, but also identify numerous factors that can dampen or prevent ultimate ecosystem consequences. Without a deeper understanding of these pathways, we risk wasting valuable resources on mitigating behavioural effects with little ecological relevance, or conversely mismanaging situations in which behavioural effects do drive ecosystem change. The framework presented here can be used to anticipate the nature and likelihood of ecological outcomes and prioritise management among widespread human‐induced behavioural shifts, while also suggesting key priorities for future research linking humans, animal behaviour and ecology.

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

Critical land change information enhances the understanding of carbon balance in the United States - Jinxun Liu; Benjamin M. Sleeter; Zhiliang Zhu; Thomas R. Loveland; Terry Sohl; Stephen M. Howard; Carl H. Key; Todd Hawbaker; Shuguang Liu; Bradley Reed; Mark A. Cochrane; Linda S. Heath; et al. (Global Change Biology, 2020)
Large‐scale terrestrial carbon (C) estimating studies using methods such as atmospheric inversion, biogeochemical modeling, and field inventories have produced different results. The goal of this study was to integrate fine‐scale processes including land use and land cover change into a large‐scale ecosystem framework. We analyzed the terrestrial C budget of the conterminous United States from 1971 to 2015 at 1‐km resolution using an enhanced dynamic global vegetation model and comprehensive land cover change data. Effects of atmospheric CO 2 fertilization, nitrogen deposition, climate, wildland fire, harvest, and land use/land cover change (LUCC) were considered. We estimate annual C losses from cropland harvest, forest clearcut and thinning, fire, and LUCC were 436.8, 117.9, 10.5, and 10.4 TgC/year, respectively. C stored in ecosystems increased from 119,494 to 127,157 TgC between 1971 and 2015, indicating a mean annual net C sink of 170.3 TgC/year. Although ecosystem net primary production increased by approximately 12.3 TgC/year, most of it was offset by increased C loss from harvest and natural disturbance and increased ecosystem respiration related to forest aging. As a result, the strength of the overall ecosystem C sink did not increase over time. Our modeled results indicate the conterminous US C sink was about 30% smaller than previous modeling studies, but converged more closely with inventory data.

Effects of Saltwater Pulses on Soil Microbial Enzymes and Organic Matter Breakdown in Freshwater and Brackish Coastal Wetlands - Shelby Servais; John S. Kominoski; Carlos Coronado-Molina; Laura Bauman; Stephen E. Davis; Evelyn E. Gaiser; Stephen Kelly; Christopher Madden; Viviana Mazzei; David Rudnik; Fabiola Santamaria; Fred H. Sklar; et al. (Estuaries and Coasts, 2020)

Adiponectin receptor agonist AdipoRon induces apoptotic cell death and suppresses proliferation in human ovarian cancer cells - Amin A. Ramzan; Benjamin G. Bitler; Douglas Hicks; Kelsey Barner; Lubna Qamar; Kian Behbakht; Theresa Powell; Thomas Jansson; Heidi Wilson (Molecular and Cellular Biochemistry, 2019)

Experimental Saltwater Intrusion Drives Rapid Soil Elevation and Carbon Loss in Freshwater and Brackish Everglades Marshes - Sean P. Charles; John S. Kominoski; Tiffany G. Troxler; Evelyn E. Gaiser; Shelby Servais; Benjamin J. Wilson; Stephen E. Davis; Fred H. Sklar; Carlos Coronado-Molina; Christopher J. Madden; Steve Kelly; David T. Rudnick (Estuaries and Coasts, 2019)

Effects of 21st‐century climate, land use, and disturbances on ecosystem carbon balance in California - Benjamin M. Sleeter; David C. Marvin; D. Richard Cameron; Paul C. Selmants; A.LeRoy Westerling; Jason Kreitler; Colin J. Daniel; Jinxun Liu; Tamara S. Wilson (Global Change Biology, 2019)
Terrestrial ecosystems are an important sink for atmospheric carbon dioxide (CO 2 ), sequestering ~30% of annual anthropogenic emissions and slowing the rise of atmospheric CO 2 . However, the future direction and magnitude of the land sink is highly uncertain. We examined how historical and projected changes in climate, land use, and ecosystem disturbances affect the carbon balance of terrestrial ecosystems in California over the period 2001–2100. We modeled 32 unique scenarios, spanning 4 land use and 2 radiative forcing scenarios as simulated by four global climate models. Between 2001 and 2015, carbon storage in California's terrestrial ecosystems declined by −188.4 Tg C, with a mean annual flux ranging from a source of −89.8 Tg C/year to a sink of 60.1 Tg C/year. The large variability in the magnitude of the state's carbon source/sink was primarily attributable to interannual variability in weather and climate, which affected the rate of carbon uptake in vegetation and the rate of ecosystem respiration. Under nearly all future scenarios, carbon storage in terrestrial ecosystems was projected to decline, with an average loss of −9.4% (−432.3 Tg C) by the year 2100 from current stocks. However, uncertainty in the magnitude of carbon loss was high, with individual scenario projections ranging from −916.2 to 121.2 Tg C and was largely driven by differences in future climate conditions projected by climate models. Moving from a high to a low radiative forcing scenario reduced net ecosystem carbon loss by 21% and when combined with reductions in land‐use change (i.e., moving from a high to a low land‐use scenario), net carbon losses were reduced by 55% on average. However, reconciling large uncertainties associated with the effect of increasing atmospheric CO 2 is needed to better constrain models used to establish baseline conditions from which ecosystem‐based climate mitigation strategies can be evaluated.

Phosphorus alleviation of salinity stress: effects of saltwater intrusion on an Everglades freshwater peat marsh - Benjamin J. Wilson; Shelby Servais; Sean P. Charles; Viviana Mazzei; Evelyn E. Gaiser; John S. Kominoski; Jennifer H. Richards; Tiffany G. Troxler (Ecology, 2019)
Saltwater intrusion and salinization of coastal wetlands around the world are becoming a pressing issue due to sea level rise. Here, we assessed how a freshwater coastal wetland ecosystem responds to saltwater intrusion. In wetland mesocosms, we continuously exposed Cladium jamaicense Crantz (sawgrass) plants and their peat soil collected from a freshwater marsh to two factors associated with saltwater intrusion in karstic ecosystems: elevated loading of salinity and phosphorus (P) inputs. We took repeated measures using a 2 × 2 factorial experimental design ( n = 6) with treatments composed of elevated salinity (~9 ppt), P loading (14.66 μmol P/d), or a combination of both. We measured changes in water physicochemistry, ecosystem productivity, and plant biomass change over two years to assess monthly and two‐year responses to saltwater intrusion. In the short‐term, plants exhibited positive growth responses with simulated saltwater intrusion (salinity + P), driven by increased P availability. Despite relatively high salinity levels for a freshwater marsh (~9 ppt), gross ecosystem productivity ( GEP ), net ecosystem productivity ( NEP ), and aboveground biomass were significantly higher in the elevated salinity + P treated monoliths compared to the freshwater controls. Salinity stress became evident after extended exposure. Although still higher than freshwater controls, GEP and NEP were significantly lower in the elevated salinity + P treatment than the +P treatment after two years. However, elevated salinity decreased live root biomass regardless of whether P was added. Our results suggest that saltwater intrusion into karstic freshwater wetlands may initially act as a subsidy by stimulating aboveground primary productivity of marsh plants. However, chronic exposure to elevated salinity results in plant stress, negatively impacting belowground peat soil structure and stability through a reduction in plant roots.

Declines in Plant Productivity Drive Carbon Loss from Brackish Coastal Wetland Mesocosms Exposed to Saltwater Intrusion - Benjamin J. Wilson; Shelby Servais; Sean P. Charles; Stephen E. Davis; Evelyn E. Gaiser; John S. Kominoski; Jennifer H. Richards; Tiffany G. Troxler (Estuaries and Coasts, 2018)

Functional and Compositional Responses of Periphyton Mats to Simulated Saltwater Intrusion in the Southern Everglades - Viviana Mazzei; Evelyn E. Gaiser; John S. Kominoski; Benjamin J. Wilson; Shelby Servais; Laura Bauman; Stephen E. Davis; Steve Kelly; Fred H. Sklar; David T. Rudnick; Jemma Stachelek; Tiffany G. Troxler (Estuaries and Coasts, 2018)

Stoichiometry patterns of plant organ N and P in coastal herbaceous wetlands along the East China Sea: implications for biogeochemical niche - Minjie Hu; Josep Peñuelas; Jordi Sardans; Zhigao Sun; Benjamin J. Wilson; Jiafang Huang; Qiuli Zhu; Chuan Tong (Plant and Soil, 2018)

Development of the Implantable Resonator System for Clinical EPR Oximetry - Rose M. Caston; Wilson Schreiber; Huagang Hou; Benjamin B. Williams; Eunice Y. Chen; Philip E. Schaner; Lesley A. Jarvis; Ann Barry Flood; Sergey V. Petryakov; Maciej M. Kmiec; Periannan Kuppusamy; Harold M. Swartz (Cell Biochemistry and Biophysics, 2017)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Seabird mortality induced by land‐based artificial lights - Airam Rodríguez; Nick D. Holmes; Peter G. Ryan; Kerry‐Jayne Wilson; Lucie Faulquier; Yovana Murillo; André F. Raine; Jay F. Penniman; Verónica Neves; Beneharo Rodríguez; Juan J. Negro; André Chiaradia; et al. (Conservation Biology, 2017)
Artificial lights at night cause high mortality of seabirds, one of the most endangered groups of birds globally. Fledglings of burrow‐nesting seabirds, and to a lesser extent adults, are attracted to and then grounded (i.e., forced to land) by lights when they fly at night. We reviewed the current state of knowledge of seabird attraction to light to identify information gaps and propose measures to address the problem. Although species in families such as Alcidae and Anatidae can be grounded by artificial light, the most affected seabirds are petrels and shearwaters (Procellariiformes). At least 56 species of Procellariiformes, more than one‐third of them (24) threatened, are subject to grounding by lights. Seabirds grounded by lights have been found worldwide, mainly on oceanic islands but also at some continental locations. Petrel breeding grounds confined to formerly uninhabited islands are particularly at risk from light pollution due to tourism and urban sprawl. Where it is impractical to ban external lights, rescue programs of grounded birds offer the most immediate and employed mitigation to reduce the rate of light‐induced mortality and save thousands of birds every year. These programs also provide useful information for seabird management. However, these data are typically fragmentary, biased, and uncertain and can lead to inaccurate impact estimates and poor understanding of the phenomenon of seabird attraction to lights. We believe the most urgently needed actions to mitigate and understand light‐induced mortality of seabirds are estimation of mortality and effects on populations; determination of threshold light levels and safe distances from light sources; documentation of the fate of rescued birds; improvement of rescue campaigns, particularly in terms of increasing recovery rates and level of care; and research on seabird‐friendly lights to reduce attraction.

A critical analysis of the direct effects of dredging on fish - Amelia S. Wenger; Euan Harvey; Shaun Wilson; Chris Rawson; Stephen J. Newman; Douglas Clarke; Benjamin J. Saunders; Nicola Browne; Michael J. Travers; Jennifer L. Mcilwain; Paul L. A. Erftemeijer; Jean‐Paul A. Hobbs; et al. (Fish and Fisheries, 2017)
Dredging can have significant impacts on aquatic environments, but the direct effects on fish have not been critically evaluated. Here, a meta‐analysis following a conservative approach is used to understand how dredging‐related stressors, including suspended sediment, contaminated sediment, hydraulic entrainment and underwater noise, directly influence the effect size and the response elicited in fish across all aquatic ecosystems and all life‐history stages. This is followed by an in‐depth review summarizing the effects of each dredging‐related stressor on fish. Across all dredging‐related stressors, studies that reported fish mortality had significantly higher effect sizes than those that describe physiological responses, although indicators of dredge impacts should endeavour to detect effects before excessive mortality occurs. Studies examining the effects of contaminated sediment also had significantly higher effect sizes than studies on clean sediment alone or noise, suggesting additive or synergistic impacts from dredging‐related stressors. The early life stages such as eggs and larvae were most likely to suffer lethal impacts, while behavioural effects were more likely to occur in adult catadromous fishes. Both suspended sediment concentration and duration of exposure greatly influenced the type of fish response observed, with both higher concentrations and longer exposure durations associated with fish mortality. The review highlights the need for in situ studies on the effects of dredging on fish which consider the interactive effects of multiple dredging‐related stressors and their impact on sensitive species of ecological and fisheries value. This information will improve the management of dredging projects and ultimately minimize their impacts on fish.

A review of the impact of pipelines and power lines on biodiversity and strategies for mitigation - Matthew L. Richardson; Benjamin A. Wilson; Daniel A. S. Aiuto; Jonquil E. Crosby; Alfonso Alonso; Francisco Dallmeier; G. Karen Golinski (Biodiversity and Conservation, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Dynamic habitat corridors for marine predators; intensive use of a coastal channel by harbour seals is modulated by tidal currents - Gordon D. Hastie; Deborah J.F. Russell; Steven Benjamins; Simon Moss; Ben Wilson; Dave Thompson (Behavioral Ecology and Sociobiology, 2016)

The population genetics of drug resistance evolution in natural populations of viral, bacterial and eukaryotic pathogens - Benjamin A. Wilson; Nandita R. Garud; Alison F. Feder; Zoe J. Assaf; Pleuni S. Pennings (Molecular Ecology, 2016)
Drug resistance is a costly consequence of pathogen evolution and a major concern in public health. In this review, we show how population genetics can be used to study the evolution of drug resistance and also how drug resistance evolution is informative as an evolutionary model system. We highlight five examples from diverse organisms with particular focus on: (i) identifying drug resistance loci in the malaria parasite Plasmodium falciparum using the genomic signatures of selective sweeps, (ii) determining the role of epistasis in drug resistance evolution in influenza, (iii) quantifying the role of standing genetic variation in the evolution of drug resistance in HIV , (iv) using drug resistance mutations to study clonal interference dynamics in tuberculosis and (v) analysing the population structure of the core and accessory genome of Staphylococcus aureus to understand the spread of methicillin resistance. Throughout this review, we discuss the uses of sequence data and population genetic theory in studying the evolution of drug resistance.

Breaking out of biogeographical modules: range expansion and taxon cycles in the hyperdiverse ant genus Pheidole - Evan P. Economo; Eli M. Sarnat; Milan Janda; Ronald Clouse; Pavel B. Klimov; Georg Fischer; Benjamin D. Blanchard; Lizette N. Ramirez; Alan N. Andersen; Maia Berman; Benoit Guénard; Andrea Lucky; et al. (Journal of Biogeography, 2015)
Aim We sought to reconstruct the biogeographical structure and dynamics of a hyperdiverse ant genus, Pheidole, and to test several predictions of the taxon cycle hypothesis. Using large datasets on Pheidole geographical distributions and phylogeny, we (1) inferred patterns of biogeographical modularity (clusters of areas with similar faunal composition), (2) tested whether species in open habitats are more likely to be expanding their range beyond module boundaries, and (3) tested whether there is a bias of lineage flow from high‐ to low‐diversity areas. Location The Old World. Methods We compiled and jointly analysed a comprehensive database of Pheidole geographical distributions, the ecological affinities of different species, and a multilocus phylogeny of the Old World radiation. We used network modularity methods to infer biogeographical structure in the genus and comparative methods to evaluate the hypotheses. Results The network analysis identified eight biogeographical modules, and a suite of species with anomalous ranges that are statistically more likely to occur in open habitat, supporting the hypothesis that open habitats promote range expansion. Phylogenetic analysis shows evidence for a cascade pattern of colonization from Asia to New Guinea to the Pacific, but no ‘upstream’ colonization in the reverse direction. Main conclusions The distributions of Pheidole lineages in the Old World are highly modular, with modules generally corresponding to biogeographical regions inferred in other groups of organisms. However, some lineages have expanded their ranges across module boundaries, and these species are more likely to be adapted to open habitats rather than interior forest. In addition, there is a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Our findings are consistent with the taxon cycle hypothesis, although they do not rule out alternative interpretations.

Genomic sequencing reveals historical, demographic and selective factors associated with the diversification of the fire‐associated fungus Neurospora discreta - Pierre Gladieux; Benjamin A. Wilson; Fanny Perraudeau; Liliam A. Montoya; David Kowbel; Christopher Hann‐Soden; Monika Fischer; Iman Sylvain; David J. Jacobson; John W. Taylor (Molecular Ecology, 2015)
Delineating microbial populations, discovering ecologically relevant phenotypes and identifying migrants, hybrids or admixed individuals have long proved notoriously difficult, thereby limiting our understanding of the evolutionary forces at play during the diversification of microbial species. However, recent advances in sequencing and computational methods have enabled an unbiased approach whereby incipient species and the genetic correlates of speciation can be identified by examining patterns of genomic variation within and between lineages. We present here a population genomic study of a phylogenetic species in the Neurospora discreta species complex, based on the resequencing of full genomes (~37 Mb) for 52 fungal isolates from nine sites in three continents. Population structure analyses revealed two distinct lineages in South–East Asia, and three lineages in North America/Europe with a broad longitudinal and latitudinal range and limited admixture between lineages. Genome scans for selective sweeps and comparisons of the genomic landscapes of diversity and recombination provided no support for a role of selection at linked sites on genomic heterogeneity in levels of divergence between lineages. However, demographic inference indicated that the observed genomic heterogeneity in divergence was generated by varying rates of gene flow between lineages following a period of isolation. Many putative cases of exchange of genetic material between phylogenetically divergent fungal lineages have been discovered, and our work highlights the quantitative importance of genetic exchanges between more closely related taxa to the evolution of fungal genomes. Our study also supports the role of allopatric isolation as a driver of diversification in saprobic microbes.

Potential future land use threats to California’s protected areas - Tamara Sue Wilson; Benjamin Michael Sleeter; Adam Wilkinson Davis (Regional Environmental Change, 2015)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

Improving the analysis of low heritability complex traits for enhanced genetic gain in potato - Anthony T. Slater; Graeme M. Wilson; Noel O. I. Cogan; John W. Forster; Benjamin J. Hayes (Theoretical and Applied Genetics, 2014)

Patterns, processes and vulnerability of Southern Ocean benthos: a decadal leap in knowledge and understanding - Stefanie Kaiser; Simone N. Brandão; Saskia Brix; David K. A. Barnes; David A. Bowden; Jeroen Ingels; Florian Leese; Stefano Schiaparelli; Claudia P. Arango; Renuka Badhe; Narissa Bax; Magdalena Blazewicz-Paszkowycz; et al. (Marine Biology, 2013)

Life cycle assessment of sponge nickel produced by gas atomisation for use in industrial hydrogenation catalysis applications - Nicholas P. Lavery; David J. Jarvis; Stephen G. R. Brown; Nicholas J. Adkins; Benjamin P. Wilson (The International Journal of Life Cycle Assessment, 2013)

The role of MHC class I allele Mamu-A*07 during SIVmac239 infection - Jason S. Reed; John Sidney; Shari M. Piaskowski; Chrystal E. Glidden; Enrique J. León; Benjamin J. Burwitz; Holly L. Kolar; Christopher M. Eernisse; Jessica R. Furlott; Nicholas J. Maness; Andrew D. Walsh; Richard A. Rudersdorf; et al. (Immunogenetics, 2011)

Estimation of late twentieth century land-cover change in California - Benjamin M. Sleeter; Tamara S. Wilson; Christopher E. Soulard; Jinxun Liu (Environmental Monitoring and Assessment, 2011)

Abnormal Fronto-striatal Connectivity in Children with Histories of Early Deprivation: A Diffusion Tensor Imaging Study - Michael E. Behen; Otto Muzik; Anita S. D. Saporta; Benjamin J. Wilson; Darshan Pai; Jing Hua; Harry T. Chugani (Brain Imaging and Behavior, 2009)

Short‐ and long‐term patterns of sponge diversity on a rocky tropical coast: evidence of large‐scale structuring factors - Jose Luis Carballo; Cristina Vega; José Antonio Cruz‐Barraza; Benjamin Yáñez; Héctor Nava; Enrique Ávila; Miroslava Wilson (Marine Ecology, 2008)
The importance of a long‐term ecological perspective is well documented, yet long‐term data are not widely available. This paper represents the first quantitative description of sublittoral sponge assemblages over long temporal scales (6 years) along the coast of the East Pacific Ocean (Mazatlan Bay), with the goal of describing their levels of intra‐ and inter‐annual variability, and their relationship to changing environmental conditions. It was possible to detect an apparent short‐term pattern (intra‐annual), with a highly diverse and stable structure, usually in the drought season, which was consistent most of the years. However, only a few species showed regular (predictable) seasonal cycles. The species per square meter (from 0.1 to 0.5), total species per sampling (14–21), and H’ diversity using log e (1.4–2) also fluctuated greatly between years, suggesting that although a consistent short‐term pattern was found most of the years, the inter‐annual variability was also high. The univariate and multivariate results and regression models indicated that local winds played a key role in this short‐term pattern (intra‐annual). During the rainy season, or during the transition between the drought and rainy season, the winds coming from the southwest (WSW) produced an increase in the net sediment movement, which was an important factor for diversity. The long‐term fluctuations (annual pattern of diversity) also correlated positively with wind speed (88% of the variance observed) and with sediment deposition (69% of the variance observed). In addition, the results indicated the existence of large‐scale structuring factors, as the annual pattern of diversity also was correlated positively with the Southern Oscillation (SOI) and Multivariate ENSO (MEI) indices (82% and 88% of the observed variance, for MEI and SOI, respectively). In conclusion, this study suggests that sponge assemblages in Mazatlán Bay are extremely dynamic, and changes in this community are associated with processes that occur over the short‐ and long‐time scales (several months to several years). The significant positive relationship between wind speed and sediment deposition showed that the main factors controlling the diversity in these shallow rocky ecosystems are the winds and the swell. A high proportion of coarse sand also indicated a very high energy in the environment, which, combined with the effect of silting, abraded and removed sponges and other organisms. These features contribute to the instability of the community by producing dramatic fluctuations in species abundance and preventing competitive processes from producing a more stable community.

Sulfur isotopic zonation in the Cadia district, southeastern Australia: exploration significance and implications for the genesis of alkalic porphyry gold–copper deposits - Alan J. Wilson; David R. Cooke; Benjamin J. Harper; Cari L. Deyell (Mineralium Deposita, 2007)

Filtering of windborne particles by a natural windbreak - Thomas Bouvet; Benjamin Loubet; John D. Wilson; Andree Tuzet (Boundary-Layer Meteorology, 2007)

Positioning of five genes (CASK, ARX, SAT, IMAGE cDNAs 248928 and 253949) from the human X Chromosome short arm with respect to evolutionary breakpoints on the mouse X Chromosome - Helen J. Blair; Vivienne Reed; Emmanuelle Gormally; Joanna B. Wilson; Jakub Novak; Roderick R. McInnes; Sandra J. Phillips; Benjamin A. Taylor; Yvonne Boyd (Mammalian Genome, 2000)

Genetic and endocrine control of renin activity in the submaxillary gland of the mouse - Carol M. Wilson; Marianna Cherry; Benjamin A. Taylor; Jean D. Wilson (Biochemical Genetics, 1981)